How COVID-19 is Changing the World : A Statistical Perspective - Committee for the Coordination of Statistical Activities (Committee for the Coordination of Statistical Activities, 2020)
The United Nations and other partner organizations of the CCSA make a wealth of impartial data and statistics available free of charge with the spirit of promoting facts-based planning. This report presents a snapshot of some of the latest information available on how COVID-19 is affecting the world today. Although a wide range of topics are covered in this report, a consistency of message is clear – this is an unprecedented crisis, and no aspect of our lives is immune. The quantitative knowledge presented in this report covers different aspects of public and private life from economic and environmental fluctuations to changes that affect individuals in terms of income, education, employment and violence and changes affecting public services such as civil aviation and postal services. The report also puts a spotlight on the affects for some sub-population groups like women and children as well as geographical regions.